2019
DOI: 10.22491/rac.2019.v32n3.7
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização fenotípica de milho pipoca conservado in situ- on farm no Extremo Oeste de Santa Catarina

Abstract: A pipoca é um tipo especial de milho e aproximadamente mil variedades locais são conservadas in situ, em propriedades rurais do Extremo Oeste de Santa Catarina (Eosc). A caracterização destas variedades é fundamental para a promoção da sua conservação, valorização e uso comercial. O objetivo deste estudo foi caracterizar a diversidade fenotípica de dez variedades de milho-pipoca desta região. Para tanto, as variedades foram avaliadas em Florianópolis, SC, em blocos completos casualizados com quatro repetições … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Another study with FWSC popcorn varieties (Seledes, Ogliari, Melhorança, Souza, & Oliveira, 2019) used varieties with different grain colors and the results corroborates with the ones found in this work, in which the white colored varieties have longer cycle and have higher average plants. The black colored varieties showed lower values for weight of one thousand grains and high prolificacy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another study with FWSC popcorn varieties (Seledes, Ogliari, Melhorança, Souza, & Oliveira, 2019) used varieties with different grain colors and the results corroborates with the ones found in this work, in which the white colored varieties have longer cycle and have higher average plants. The black colored varieties showed lower values for weight of one thousand grains and high prolificacy.…”
Section: Discussionsupporting
confidence: 86%
“…In the work of Barbano, Sawazaki, Brunini, and Boller (2003), evaluating three commercial popcorn cultivars, the authors found that all materials accumulated, on average, less than 800 ADD for tasseling. Seledes et al (2019) observed that the FWSC populations with withe grains presented higher values of ADD for tasseling (up to 1007 ADD).…”
Section: Discussionmentioning
confidence: 91%
“…These indices indicate the rounded shape of the grains and have a positive correlation with the expansion capacity. Grains with greater symmetry between dimensions had CCI values close to 0.5 (Seledes et al, 2019). A (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i8.17141 close value was observed for some LP grains (0.48).…”
Section: Physical Properties Of the Lpmentioning
confidence: 68%
“…The values obtained for the thickness/width ratio and CCI of LP were 0.62 (0.39-1.01) and 0.27 (0.18-0.48), respectively. By studying popcorn landraces in southern Brazil, Gonçalves et al (2019) and Seledes et al (2019) reported CCI values between 0.28-0.30 and 0.27-0.35, respectively; and between 0.60-0.82 for the thickness/width ratio observed by Gonçalves and colleagues. These indices indicate the rounded shape of the grains and have a positive correlation with the expansion capacity.…”
Section: Physical Properties Of the Lpmentioning
confidence: 86%